Implementing whole of chain analysis for the seafood industry: A toolbox approach - Howieson, Janet; Lawley, Meredith (Department of Management, College of Business and Economics, University of Canterbury, 2010)
Whole of chain analyses are increasingly recognised as an important tool for improving the efficeincy and effectiveness of agri-food chains, particularly in industries where many producers are small, family-owned businesses. However, there remains confusion in the literature and in practice about the different approaches that can be taken to whole of chain analysis. The purpose of this paper is two-fold: firstly to define and describe the various approaches to analyses of food chains, and secondly, to provide a set of principles and a decision tree from which food industry companies can choose their preferred whole of chain activity based on their intended outcomes. This paper will use the seafood industry as an exemplar, noting that principles could apply across other primary production sectors.